Web 2.0 and social networks: a study of scientific publications in Spanish communication journals - Ramos Soler, Irene; del Pino Romero, Cristina; Castelló Martínez, Araceli (Historia y Comunicación Social, 2014)
Communication and advertising currently live immersed in a process of change and constant evolution, powered by social, cultural and technological revolution that web 2.0 has brought. This work aims to determine the main lines of academic work in the field of social networks and web 2.0 in Spain, studying the projection and the use given to each of the scientific research methodologies. To carry out the analysis it has been done a selection of publications on this topic in major communication journals of Spain.
Keywords: journals; social networks; web 2.0; communication; internet.